2004
DOI: 10.1074/jbc.m405985200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Assembly of Inwardly Rectifying K+ Channel Subunits, Kir4.1 and Kir5.1, in Brain Astrocytes

Abstract: The inwardly rectifying K ؉ channel subunit Kir5.1 is expressed abundantly in the brain, but its precise distribution and function are still largely unknown. Because Kir5.1 is co-expressed with Kir4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
145
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(156 citation statements)
references
References 54 publications
9
145
1
1
Order By: Relevance
“…The downregulation of Cx43 observed in FACS-purified GFAP-EGFP + astrocytes was analyzed further, because of: (i) the fundamental physiological role of Cx43 as the main gap junction channel in astrocytes (Dermietzel et al, 1991;Iacobas et al, 2004); (ii) the downregulation of Cx43 also found in cortical tissue of hyperammonemic mice (present study); (iii) the clustering and apparent loss of connectivity between EGFP + astrocytes along the brain vasculature of hyperammonemic animals (present study); and (iv) the importance of Cx43 for potassium homeostasis in the brain (Kozoriz et al, 2006;Wallraff et al, 2006). In addition to Cx43 and gap junctions, potassium homeostasis is also regulated by astrocytic inward-rectifying potassium channels, which exist as Kir4.1 homodimers and Kir4.1/Kir5.1 heterodimers (Hibino et al, 2004;Kofuji et al, 2002;Kucheryavykh et al, 2007;Neusch et al, 2006). In the mouse neocortex, the heteromeric Kir4.1/Kir5.1 channel was detected perivascularly, and both the homomeric Kir4.1 and heteromeric Kir4.1/Kir5.1 channel were found in perisynaptic astrocytic processes (Hibino et al, 2004).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…The downregulation of Cx43 observed in FACS-purified GFAP-EGFP + astrocytes was analyzed further, because of: (i) the fundamental physiological role of Cx43 as the main gap junction channel in astrocytes (Dermietzel et al, 1991;Iacobas et al, 2004); (ii) the downregulation of Cx43 also found in cortical tissue of hyperammonemic mice (present study); (iii) the clustering and apparent loss of connectivity between EGFP + astrocytes along the brain vasculature of hyperammonemic animals (present study); and (iv) the importance of Cx43 for potassium homeostasis in the brain (Kozoriz et al, 2006;Wallraff et al, 2006). In addition to Cx43 and gap junctions, potassium homeostasis is also regulated by astrocytic inward-rectifying potassium channels, which exist as Kir4.1 homodimers and Kir4.1/Kir5.1 heterodimers (Hibino et al, 2004;Kofuji et al, 2002;Kucheryavykh et al, 2007;Neusch et al, 2006). In the mouse neocortex, the heteromeric Kir4.1/Kir5.1 channel was detected perivascularly, and both the homomeric Kir4.1 and heteromeric Kir4.1/Kir5.1 channel were found in perisynaptic astrocytic processes (Hibino et al, 2004).…”
Section: Discussionmentioning
confidence: 62%
“…In addition to Cx43 and gap junctions, potassium homeostasis is also regulated by astrocytic inward-rectifying potassium channels, which exist as Kir4.1 homodimers and Kir4.1/Kir5.1 heterodimers (Hibino et al, 2004;Kofuji et al, 2002;Kucheryavykh et al, 2007;Neusch et al, 2006). In the mouse neocortex, the heteromeric Kir4.1/Kir5.1 channel was detected perivascularly, and both the homomeric Kir4.1 and heteromeric Kir4.1/Kir5.1 channel were found in perisynaptic astrocytic processes (Hibino et al, 2004). Kir4.1 was also shown to be part of a plasma membrane dystroglycan complex that includes Aqp4 (Hibino et al, 2004;Kofuji and Newman, 2004), Agp4 the main astrocytic water channel at the brain vasculature and key to water homeostasis in brain (Badaut et al, 2002;Solenov et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations